2008
DOI: 10.1523/jneurosci.1600-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Reward Delays on Responses of Dopamine Neurons

Abstract: Psychological and microeconomic studies have shown that outcome values are discounted by imposed delays. The effect, called temporal discounting, is demonstrated typically by choice preferences for sooner smaller rewards over later larger rewards. However, it is unclear whether temporal discounting occurs during the decision process when differently delayed reward outcomes are compared or during predictions of reward delays by pavlovian conditioned stimuli without choice. To address this issue, we investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
371
7
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 396 publications
(431 citation statements)
references
References 41 publications
42
371
7
1
Order By: Relevance
“…The most thorough examination of this frequency band in the behaving rodent may be that of Fujisawa and Buzsáki (2011), who found that coherence between 2 and 5 Hz increased between the ventral tegmental area (VTA) and prelimbic cortex during an odor-to-place matching task, and that this oscillation was phase-coupled with theta in the dorsal hippocampus. This report extended previous observations that VTA neurons often fire action potentials at regular intervals of 4 Hz (Hyland et al, 2002;Paladini and Tepper, 1999;Bayer et al, 2007;Dzirasa et al, 2010;Kobayashi and Schultz, 2008). Hippocampal-prefrontal coherence in the 4 Hz band can also increase when dopamine is injection directly into the prefrontal cortex (Benchenane et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…The most thorough examination of this frequency band in the behaving rodent may be that of Fujisawa and Buzsáki (2011), who found that coherence between 2 and 5 Hz increased between the ventral tegmental area (VTA) and prelimbic cortex during an odor-to-place matching task, and that this oscillation was phase-coupled with theta in the dorsal hippocampus. This report extended previous observations that VTA neurons often fire action potentials at regular intervals of 4 Hz (Hyland et al, 2002;Paladini and Tepper, 1999;Bayer et al, 2007;Dzirasa et al, 2010;Kobayashi and Schultz, 2008). Hippocampal-prefrontal coherence in the 4 Hz band can also increase when dopamine is injection directly into the prefrontal cortex (Benchenane et al, 2010).…”
Section: Discussionsupporting
confidence: 88%
“…For instance, the magnitude of the change in DA neuron activity was recently shown to be modulated by the size of the reward prediction error and by the length of the stimulus-reward interval, such that the most valuable reward induced the greatest increase in neural activity (Kobayashi and Schultz 2008;Roesch et al 2007). This is in line with the TD model, which incorporates a discount factor to take these magnitude differences into account.…”
Section: Temporal Difference Modelmentioning
confidence: 57%
“…This is again in line with the theoretical formulation as the expected value increases with the size of the reward and its probability. Furthermore, the longer the delay between the CS and the reward, the weaker the response (Fiorillo et al, 2008;Kobayashi and Schultz, 2008;Roesch et al, 2007), reflecting temporal discounting of future rewards. Finally, if a reward-predicting stimulus is itself preceded by another, earlier, stimulus, then the phasic activation of dopamine neurons transfers back to this earlier stimulus (Schultz et al, 1993), which is again captured by the above theoretical account (Montague et al, 1996) of model-free learning.…”
Section: Phasic Dopamine Signals Represent Model-free Prediction Errorsmentioning
confidence: 99%